The Engineering Properties Of Fly Ash - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
. ABSTRACT Power stations using coal as a fuel-are important in many countries. Fly ash is a waste product of coal burning power station, and as a waste presents a considerable problem to power station because it has to be stored or disposed. It can be an environmental problem. To solve the problem, it is necessary to promote the use of fly ash as more beneficial material. This research aims to study the engineering properties of fly ash as pavement subgrade material, embraces the study of index properties, compaction characteristics, CBR value and swelling potential, and permeability. Materials used were conditioned fly ash and stockpiled fly ash from Tilbury Power Station. The index properties of ashes were tested in accordance with the British Standard 1377:1975, the chemical composition, particle shape and texture were investigated using scanning electron microscope. Compaction characteristics were studied using vibrating hammer. method as described in the British Standard. The soaked CBR and permeability tests were conducted to the samples cured for 0, 7, 14, 21, and 28 days. The results showed that the fly ashes under investigation are described as sandy SILT, lightweight and non-plastic material. The soaked CBR values and swelling results of both two fly ashes samples exhibited that the are similar to that of field CBR value of gravel and gravelly soils, and practically has no swelling. The coefficient of permeability of the samples was very low and the material could be classes as practically impervious material.